KSHV induces immunoglobulin rearrangements in mature B lymphocytes. - Jennifer Totonchy; Jessica M Osborn; Amy Chadburn; Ramina Nabiee; Lissenya Argueta; Geoffrey Mikita; Ethel Cesarman (PLoS Pathogens, 2018)
Kaposi sarcoma herpesvirus (KSHV/HHV-8) is a B cell tropic human pathogen, which is present in vivo in monotypic immunoglobulin λ (Igλ) light chain but polyclonal B cells. In the current study, we use cell sorting to infect specific B cell lineages from human tonsil specimens in order to examine the immunophenotypic alterations associated with KSHV infection. We describe IL-6 dependent maturation of naïve B lymphocytes in response to KSHV infection and determine that the Igλ monotypic bias of KSHV infection in vivo is due to viral induction of BCR revision. Infection of immunoglobulin κ (Igκ) naïve B cells induces expression of Igλ and isotypic inclusion, with eventual loss of Igκ. We show that this phenotypic shift occurs via re-induction of Rag-mediated V(D)J recombination. These data explain the selective presence of KSHV in Igλ B cells in vivo and provide the first evidence that a human pathogen can manipulate the molecular mechanisms responsible for immunoglobulin diversity.